FENOMENA PENYALAHGUNAAN TAMAN SEBAGAI TEMPAT SEX BEBAS (Studi Kasus Desa Berapit Luar Kecamatan Seberida, Kabupaten Indragiri Hulu) - Askarial; M. Hanafi (UIR PRESS, 2021)
Good and proper social behavior there are valid norms, both legal and social norms, that in social behavior there are some deviations, one of which is a case of misappropriation of the park as a place of casual sex where a youth in search of an identity has fallen into casual sex and the park's abuse is not free of the lack of social control. Most societies allow society as a society of nurturing and supportive of these young people, on the other hand, the loss of parental control as the smallest organization in social social structure that influences growth, where children view dating as a normal matter, resulting in their further deterioration of sexual promiscuity. Therefore, to save next generation communities and families are asked to be procuring supplies as the basis for creating a sustainable future generation.